Responsible practices in the wild: an actor-network perspective on mobile apps in learning as translation(s) - Laasch, Oliver; Moosmayer, Dirk C.; Arp, Frithjof (Springer, 2019)
Competence to enact responsible practices, such as recycling waste or boycotting irresponsible companies, is core to learning for responsibility. We explore the role of apps in learning such responsible practices ‘in the wild,’ outside formal educational environments over a 3-week period. Learners maintained a daily diary in which they reflected on their learning of responsible practices with apps. Through a thematic analysis of 557 app mentions in the diaries, we identified five types of app-agency: cognitive, action, interpersonal, personal development, and material. Findings were interpreted from an actor-network perspective using the lens of ‘translation.’ To understand how apps enabled the learning of responsible practices, we analyzed app agency throughout four moments of translation: problematization, interessement, enrolment, and mobilization. Based on our analysis of how students’ app mentions changed over time, we further theorize learning as a sequence of subtranslations that form the larger translation process: learning as translation(s). Each subtranslation cycle is centered on enrolling a different set of human and nonhuman actors, with their competence, into the network. We contribute to the learning for responsibility field by showcasing how app-enabled learning may create real-life actor networks enacting responsibility, and by priming an actor-network pedagogy for ‘learning in the wild.’ We also contribute to the actor-network learning discussion by conceptualizing heterogeneous human–nonhuman competence and the first processual model of learning as translation(s).